2005
DOI: 10.1007/s00334-005-0026-6
|View full text |Cite
|
Sign up to set email alerts
|

Human impact during the Bronze Age on the vegetation at Lago Lucone (northern Italy)

Abstract: Lake-sediment records were used to reconstruct human impact on the landscape around Lago Lucone (45 • 33 N, 10 • 29 E, 249 m a.s.l.), a former lake in the western amphitheatre system of the Lago di Garda. Presence of prehistoric human populations is attested by pile-dwelling settlements from the Early-Middle Bronze Age, with one settlement at a distance of only 100 m from the coring site. Pollen, plant-macrofossil and microscopic charcoal analyses were applied to a 250 cm sediment core with four dates providin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 33 publications
2
48
0
2
Order By: Relevance
“…This situation is not consistent with the main Bronze Age societies in southern Europe, where one of the features linked with the social change occurring in this period is the large-scale impact on the landscape, as at El Argar in the south-eastern Iberian Peninsula (Castro et al, 2000;Carrión et al, 2007), and other European regions like central Italy (Sadori et al, 2004), northern Italy (Valsecchi et al, 2006) and north-eastern Bulgaria (Marinova and Atanassova, 2006). This invisibility of Bronze Age communities could be due to the scarce archaeological record belonging to this phase in the surroundings of Lake Banyoles, and also to the fact that Bronze Age communities did not base their economy on metallurgical production, which may have been a secondary activity (Rovira, 2006).…”
Section: Land Use and Human Impact During Late Prehistory In The Lakementioning
confidence: 60%
“…This situation is not consistent with the main Bronze Age societies in southern Europe, where one of the features linked with the social change occurring in this period is the large-scale impact on the landscape, as at El Argar in the south-eastern Iberian Peninsula (Castro et al, 2000;Carrión et al, 2007), and other European regions like central Italy (Sadori et al, 2004), northern Italy (Valsecchi et al, 2006) and north-eastern Bulgaria (Marinova and Atanassova, 2006). This invisibility of Bronze Age communities could be due to the scarce archaeological record belonging to this phase in the surroundings of Lake Banyoles, and also to the fact that Bronze Age communities did not base their economy on metallurgical production, which may have been a secondary activity (Rovira, 2006).…”
Section: Land Use and Human Impact During Late Prehistory In The Lakementioning
confidence: 60%
“…Compared with the Neolithic, later human impact on the landscape became more intense, with more extensive cultivation and animal husbandry, accompanied by a development towards more complex societies (Castelletti et al, 2001). The vegetation pattern of nearby sites in Trentino (Valsecchi et al, 2006) suggested that the landscape has been exposed to more intense human impact since about 2000 BC. The human presence in the Bronze Age is supported by several finds of artefacts in Alpine valleys in Austria, Germany and Trentino (Finsinger, 2001;Schmidl et al, 2005;Eckmeier et al, 2007).…”
Section: (2) Copper Bronze and Early Iron Agementioning
confidence: 99%
“…Archaeological studies have demonstrated the continuous presence of complex human societies in these valleys from the Mesolithic period (c. 8000-4500 cal. BP) until modern history (eg, Cucina et al, 1999;Schmidl et al, 2005;Valsecchi et al, 2006). This study focuses on the identification and dating of charcoal fragments extracted from nine Alpine and sub-Alpine soils.…”
Section: Introductionmentioning
confidence: 99%
“…A strong reduction of forest cover was observed in coincidence with the establishment of the Late Neolithic pile-dwelling settlement at Palù di Livenza (Northern Italy; Pini, 2004), and other Bronze Age settlements in Central and Northern Italy (Bertolani Marchetti et al, 1988;Nisbet and Rottoli, 1997;Sadori et al, 2004;De Marinis et al, 2005;Cremaschi et al, 2006;Mercuri et al, 2006;Valsecchi et al, 2006;Magny et al, 2009).…”
Section: Discussionmentioning
confidence: 94%